Perceived Susceptibility and Perceived Benefit as Factors Affecting VIA Tests Participation in Work Area of Kertosari Health Center - Kurnia Nata Pratiwi; Sri Hernawati; Dewi Rohkmah (Health Notions, 2018)
In Indonesia, cervical cancer is ranked first as the cause of death to women. The government has implemented an early detection program of cervical cancer in controlling cervical cancer by using Visual Inspection with Acetic Acid (VIA). Indonesian women's awareness to perform early detection is still very low with coverage of early detection of cervical cancer which is less than 5%. The Health Belief Model (HBM) is used to forecast health enhancement behavior that is based on individual behavior determined by the individual's motives and beliefs. The purpose of this study was to analyze the effect of Health Belief Model (HBM) which included perceived of susceptibility, perceived of severity, perceived of benefits, perceived of threats, perceived of barriers and cues to act on VIA test participation. This type of research was observational analytics. The design used was case control. The sample in this study were 64 cases and 64 controls, selected by purposive sampling. Data were analyzed using Partial Least Square (PLS). Based on the result of research, there was an influence of perceived of susceptibility on participation with t value = 4.417 (>1.96). Perceived of benefit affected participation with t value = 11.647 (>1.96). Keywords: Perceived susceptibility, Perceived severity, Perceived threat, Perceived benefit, Perceived barrier, Cues to action, VIA test